Portraits of Well-Being: Photography as a Mental Health Support for Women With HIV. Issue 1 (2nd January 2017) - Teti, Michelle; French, Bryana; Kabel, Allison; Farnan, Rose
ABSTRACT: Many women living with HIV/AIDS (WL-HIV/AIDS) experience significant mental distress. Although creative arts strategies are well positioned to help support women by inspiring creativity and meaning-making, few arts programs have been implemented and evaluated with this population. The authors conducted a photography project with 30 WL-HIV/AIDS from three United States cities. Participants took pictures to capture their lives with HIV/AIDS and described their photos and stories in group and individual sessions. Using thematic analysis, the authors identified that the project supported women's mental health in four ways by facilitating empowerment and helping women to express themselves, address their mental health with new tools like photography, and process past traumas. Photography projects may help WL-HIV/AIDS understand and manage their mental health.